2018
DOI: 10.1159/000496044
|View full text |Cite
|
Sign up to set email alerts
|

Jagged1 is Clinically Prognostic and Promotes Invasion of Glioma-Initiating Cells by Activating NF-κB(p65) Signaling

Abstract: Background/Aims: Jagged1 is the ligands of the Notch signaling and has been shown to promote glioma-initiating cells (GICs) in glioblastoma. The role of Jagged1 in GICs invasion and underlying molecular mechanisms remain unclear. Methods: Survival data from R2 genomics analysis, the Cancer Genome Atlas (TCGA), the Chinese Glioma Genome Atlas (CGGA) and visualization platform database were used to evaluate the effects of Jagged1 on overall patient survival. we investigated Jagged1 induced the GICs cells’ invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Notch signaling mediates direct cell-cell interactions and plays a crucial part in cell fate maintenance and selfrenewal of GICs (107). Moreover, studies have shown that down-regulation of Jagged1 induces apoptosis and inhibits proliferation in glioma cell lines (108). Similarly, different variants of OCT4 (POU5F1) have been related to colony formation and regulation of cell survival in GSC (109).…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling mediates direct cell-cell interactions and plays a crucial part in cell fate maintenance and selfrenewal of GICs (107). Moreover, studies have shown that down-regulation of Jagged1 induces apoptosis and inhibits proliferation in glioma cell lines (108). Similarly, different variants of OCT4 (POU5F1) have been related to colony formation and regulation of cell survival in GSC (109).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by screening for possible signaling pathways using a dual luciferase reporter assay (Figure S6), we found that the LKB1 gene regulated NF-κB signaling, which plays important roles in cancer growth and metastasis. P65 is a regulatory transcription factor particularly vital in cell survival, growth, and differentiation 21,22. NF-κB activation blocked Snail degradation, subsequently promoting cancer cell migration and invasion 23,24.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatoblastoma (HB), a malignant embryonic tumor, is a common liver tumor in children. Liu’s study used gene sequencing to detect the differential expression of circRNA in the HB tissue and adjacent tissue [ 32 ]. They found a substantially upregulated expression of circ_0015756 in HB tissues.…”
Section: Circrna and Common Smts In Childrenmentioning
confidence: 99%